Perceived psychosocial job stress and sleep bruxism among male and female workers - Nakata A, Takahashi M, Ikeda T, Hojou M, Araki S. (Journal compilation, 2008)
Psychosocial job stress has been associated with sleep disturbances, but its association with sleep bruxism (SB), the stereotype movement disorder related to sleep, is not well understood